PEMETAAN KAPASITAS PESANTREN DI KOTA PALU PROVINSI SULAWESI TENGAH - Sofyan Sofyan (EDUCANDUM, 2018)
The Mapping Capacity Study of Islamic Boarding Schools in CentralSulawesi, one of them is in the Palu City targeting all pesantren. Usingdescriptive method. The research aims to map the distribution ofpesantren, the main elements in pesantren include kiai, scripture study,santri, mushallah / mosque, dormitory, also about empowerment andplanting national values. The study found that pesantren had not spreadto all districts. The five main elements that are expected to be owned bypesantren, are only owned by some pesantren. Empowerment andcultivation of national values have not been optimized because of theneed for cross-pesantren networks and intense coordination from theMinistry of Religion of Palu City